RANCANGAN SISTEM KELISTRIKAN PLTS OFF GRID 1000 WATT DI DESA LOEHA KECAMATAN TOWUTI - Muhammad Naim (VERTEX ELEKTRO, 2020)
One solution to solve electrical problems in Loeha village in Towuti sub-district is the provision of new and renewable energy source which is environmentally friendly as an alternative to the addition of electricity supply that is PLTS Off Grid electrical system. The purpose of this research is to design the electrical system of Off Grid PLTS with the capacity of 1000 Watt in Loeha village, Towuti sub-district, East Luwu regency so that later can overcome the electrical problems that happened in this region. The results show that the equipment needed to support the electrical system. PLTS Off Grid 1000 Watt is Photovoltaic (PV) or Solar cell amount to 4 pieces with technical specification; type cell monocrytalline, cell efficiency 15%, maximum power 260 Wp. Solar Charge Controller using MPPT technology with technical specifications; working voltage PV max 140 VDC, battery working voltage 48 VDC, Output Current max 60 A, efficiency 97%, and 1000 Watt capacity. Battery bank Deep cycle with technical specifications; type Deep Cycle OPzV battery, nominal voltage 2 V / cell, Cycle life 1200, DOD 80%, and capacity 160 Ah. And Bidirectional inverters with Technical Specifications; DC input Volt (nominal) 50.4 V, Voltage limit input 40-64 V, Current input 131 A, Charging Current 100 A, Type of signal True Sine Wave 50 Hz, Continous Output Power 1 KVA.